2000
DOI: 10.1577/1548-8675(2000)020<0010:uossos>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Strain, Season of Stocking, and Size at Stocking to Improve Fisheries for Rainbow Trout in Reservoirs with Walleyes

Abstract: We evaluated stockings of rainbow trout Oncorhynchus mykiss in Pathfinder and Alcova reservoirs, Wyoming, to determine what combination of strain, season of stocking, and size at stocking maximized angler catch in the presence of walleyes Stizostedion vitreum. Coded wire tags were used to identify individual rainbow trout to stock group. Angler catch of Kamloops rainbow trout and fall rainbow trout in Pathfinder Reservoir exceeded returns of Eagle Lake rainbow trout. Differences in strain performance in Alcova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 19 publications
1
48
1
Order By: Relevance
“…For example, it has been suggested that stocking trout in the fall increases survival because warm-and cool-water predators such as largemouth bass and walleye become less active (Wiley et al 1993, Yule et al 2000. However, we observed largemouth bass predation on rainbow trout to occur only during the fall due to spatial habitat overlap and stocking of vulnerable sized fish.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, it has been suggested that stocking trout in the fall increases survival because warm-and cool-water predators such as largemouth bass and walleye become less active (Wiley et al 1993, Yule et al 2000. However, we observed largemouth bass predation on rainbow trout to occur only during the fall due to spatial habitat overlap and stocking of vulnerable sized fish.…”
Section: Discussioncontrasting
confidence: 55%
“…Throughout the United States, millions of rainbow trout are stocked annually as sport fish in put-and-take fisheries; however, we have known for more than 50 years that stocked rainbow trout are highly susceptible to predation (Johnson and Hasler 1954), and more recently they have been shown to end up as the primary forage base for piscivores (Marwitz and Hubert 1997, Yule et al 2000, Flinders and Bonar 2008. Additionally, elevated body condition of top predators is correlated with the stocking of rainbow trout (Marwitz andHubert 1997, Flinders andBonar 2008), and exceptional growth rates of top predators have been related to the availability of soft-rayed prey fishes with high energy density and minimal handling time, such as rainbow trout (Beyerle 1971, Johnson andMartinez 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, angler catch of hatchery trout stocked in lentic environments is affected by numerous factors other than pelican predation, such as rearing conditions in the hatchery (e.g., Davison 1997; Barnes et al 2009), season of stocking and size at release (Yule et al 2000), water quality (Koenig and Meyer 2011), and the presence of piscine and other avian predators (Derby and Lovvorn 1997). Thus a low rate of pelican predation would not necessarily translate directly into high rates of angler catch.…”
mentioning
confidence: 99%